EPC-business.com: the benefits and challenges of implementing e-procurement / Norazlin A. Manaf - A. Manaf, Norazlin (2005)
Business organizations could take advantage of the significant arrival of Internet technology that has prompted various innovative applications. Electronic Procurement or e-Procurement is a method of procurement using the electronic catalog and automated workflow processes, is among the critical business application that used the Internet technology tools. The e-procurement are conducted electronically via a low cost technology co-called the Internet which are involving various processes in procurement cycle such as Product Requisition, Selection Of Order, Issuance Of RFQ, Purchase Order Acknowledgement, Evaluation Of Proposal, Negotiation /Award Of Contract, Issuance Of Purchase Order, Fulfillment of Orders and Payment Of Order. E-procurement is the first important step to realize the integration between electronic tools and procurement cycle in the development of procurement activity in Malaysia. The new wave of global procurement will in corporate a higher quality standard that has to be abided with by the suppliers and manufacturers alike. E-procurement is predicted to improve efficiency in the usage of resources and hence reduce the production cost in Malaysian industries. It will help organizations to improve the quality and add value to their products as well. This study will proceed to look upon the challenges and the benefits arise from implementing the e-procurement in Malaysian industries.